STRATEGI KOMUNIKASI PEMASARAN SHOPEE DALAM MEMBANGUN POSITIONING DI TENGAH PANDEMI COVID-19 DI INDONESIA - Priyo Suswanto; Sri Dewi Setiawati (Linimasa : Jurnal Ilmu Komunikasi, 2020)
ABSTRACT In the middle of the Covid-19 pandemic, people are required to carry out their activities from home and avoid direct social interaction in according to government recommendations. In supporting the government program Shopee declared as a warrior of Shopping from home with the campaign program called #ShopeeDariRumah. The purpose of this research is to analyze Shopee marketing communication strategy in the middle of the Covid-19 pandemic which requires people to reduce direct social interaction and faced intense e-commerce competition in Indonesia. In this case the researcher uses a case study approach with qualitative research methods. The results of this research is based by utilizing new media that were adopted into Shopee media features owned by Shopee, were supported by using rational, emotional and moral message content idea strategies through the use of media and appropriate consumer loopholes based on the requirements for positioning, Shopee succeeded get the attention of consumers and care in the eyes of its users, so that positioning is directly formed among the customers, especially the Indonesian citizen.